Changing-Look AGNs or Short-Lived Radio Sources? - Wołowska, Aleksandra; Kunert-Bajraszewska, Magdalena; Mooley, Kunal; Hallinan, Gregg (Frontiers in Astronomy and Space Sciences, 2017)
The evolution of extragalactic radio sources has been a fundamental question in the study of active galactic nuclei for many years. A standard evolutionary model has been created based on observations of a wide range of radio sources. In the general scenario of the evolution, the younger and smaller Gigahertz-Peaked Spectrum (GPS) and Compact Steep Spectrum (CSS) sources become large-scale FRI and FRII objects. However, a growing number of observations of low power radio sources suggests that the model cannot explain all their properties and there are still some aspects of the evolutionary path that remain unclear. There are indications}, that some sources may be short-lived objects on timescales of $10^4$ - $10^5$ years. Those objects represent a new population of active galaxies. Here, we present the discovery of several radio transient sources on timescales of 5-20 years, largely associated with renewed AGN (Active Galactic Nucleus) activity. These changing-look AGNs possibly represent behaviour typical for many active galaxies.